The reality of the practice of leadership distributed by the leaders of public education schools in the urban city of Abha from the point of view of teachers and administrators - Al-Bahish, Azzah Abdullah Hassan; Al-Badawi, Amal Mohammed Hassan (Journal of Educational and Psychological Sciences, 2022)
The research aimed to identify the reality of the practice of distributed leadership among general education school leaders in the urban city of Abha. The practice of distributed leadership among general education school leaders in the urban city of Abha on a total average (2.93 out of 5), that is, at a (medium) degree and at the level of sub-dimensions; The school vision dimension came in the first place with a mean of (2.96), the school culture dimension with an average of (2.93) and the third dimension of joint responsibility with an average of (2.88), all with a verbal rating (medium), and the results showed that there were no statistically significant differences attributed to the current job variable, and Years of service, while there were statistically significant differences for the dimensions of school culture and shared responsibility attributed to the variable years of service in favor of ten years or more. Urban with specialists experts, and consultants in modern educational leadership trends.